In Secondary diverse students require different educational answers (Journal of Parents and Teachers, 2013)
Taking into account the curricular difficulties and the complex organization and great number of teachers; it is possible to continue with the special needs program in Secondary if  there is an appropriate an flexible organization. Besides the special needs students need to be provided with specific means and tools which may enable them to continue their personal; social and educational development  and personal autonomy.In this context;  special needs students should be allowed to choose their own friends either from the big group or from the special needs group and should be respected in their choices and opinions.
Keywords: Secondary; special needs; flexible organization; Family and disabilities